Interpretation of Message and Religious Fanaticism Among Generation Z - Insani, Galang Nur; Rohmah, Ainun Ni'matu; Dwivayani, Kadek Dristiana; Nurliah , Nurliah (Jurnal Indonesia Sosial Sains, 2025)
Generation Z, as active users of social media, especially YouTube, has great potential in absorbing and interpreting religious messages. This study aims to analyze how students of the Mulawarman University Center for Islamic Studies interpret religious messages delivered through Ustadz Khalid Basalamah'. s YouTube channel, as well as their relationship with religious fanaticismA qualitative phenomenological approach is used to explore the meaning of messages based on the theorystimulus-organism-response (S-O-R) . Data were collected through in-depth interviews with selected informants using methodpurposive sampling, and supported by observation. The results showed that YouTube acts as the main media for informants to access complete religious studies. At the stimulus stage, individual beliefs and needs influence the meaning of the message. At the stageorganism , informants process messages according to their preferences and form responses that reflect their beliefs. The resulting responses vary from attitude change to fanaticism. Social media is proven to change individuals' religious views, ways of thinking and attitudes. However, a superficial understanding of messages can lead to fanaticism. This research emphasizes the importance of deep understanding in interpreting religious messages, in order to prevent negative impacts such as excessive fanaticism.